The Role Of The Financial Services Authority (OJK) In Supervising The Financial Of Sharia Transactions - Moh Mardi (Journal of Social Science and Economics, 2022)
This study aims to determine the role of the Financial Services Authority in supervising Islamic financial transactions (Financial Technology) in conducting buying and selling transactions using Sharia and assisting the public in choosing Sharia that is safe and licensed from the OJK. This research method uses a qualitative approach by conducting content analysis techniques from the results of previous studies in the form of reputable journals so as to produce an analysis that focuses on the role of OJK in the financial supervision of Islamic transactions. From this analysis, it is concluded that OJK has been optimal in taking preventive actions and can minimize transaction fraud, especially financial transactions that are Sharia transactions, therefore the OJK's role and repressive actions are quite maximal because they are firm in closing down transaction companies that have the potential to be fraudulent and detrimental.